An exploratory investigation of the organizational impacts of collaborative information technology utilization in Australian organizations - Bajwa, D.; Pervan, Graham; Lewis, L. (Shidler College of Business, University of Hawaii at Manoa, 2010)
In this paper, we extend the existing literature by exploring the organizational-level impacts of Collaborative Information Technology (CIT). We consider CIT as any information technology (IT) that supports collaboration tasks. Data was collected from 73 organizations in Australia to access organizational impacts of CITs. Our results indicate that CIT use for primary collaborative tasks (information and knowledge sharing, decision-making, report writing/information pooling), secondary collaborative tasks (communications, scheduling, and monitoring progress), and tertiary collaborative tasks (issue resolution and discussion and brainstorming) is positively and significantly associated with strategic, efficiency-oriented, and effectiveness-oriented organizational level impacts. Implications of our findings are discussed for practice and research.